Narrating the Pilgrimage to Mecca Historical and Contemporary Accounts - Buitelaar, Marjo; van Leeuwen, Richard (Brill, 2023)
Narrating the pilgrimage to Mecca discusses a wide variety of historical and contemporary personal accounts of the pilgrimage to Mecca, most of which presented in English for the first time. The book addresses how being situated in a specific cultural context and moment in history informs the meanings attributed to the pilgrimage experience. The various contributions reflect on how, in their stories, pilgrims draw on multiple cultural discourses and practices that shape their daily lifeworlds to convey the ways in which the pilgrimage to Mecca speaks to their senses and moves them emotionally. Together, the written memoirs and oral accounts discussed in the book offer unique insights in Islam's rich and evolving tradition of hajj and ʿumra storytelling. Contributors Kholoud Al-Ajarma, Piotr Bachtin, Vladimir Bobrovnikov, Marjo Buitelaar, Nadia Caidi, Simon Coleman, Thomas Ecker, Zahir Janmohamed, Khadija Kadrouch-Outmany, Ammeke Kateman, Yahya Nurgat, Jihan Safar, Neda Saghaee, Leila Seurat, Richard van Leeuwen and Miguel Ángel Vázquez.